The Lineage Status of Children Born Out of Wedlock: A Comparative Analysis of Islamic Jurisprudence and Indonesian Law - Deris Arista Saputra; Zul-kifli Hussin (SETYAKI : Jurnal Studi Keagamaan Islam, 2025)
The purpose of this study is to examine the legal status of children born out of wedlock by comparing the concept of lineage (nasab) in classical Islamic jurisprudence with its interpretation under Indonesian law. The issue is complex, situated at the intersection of religious doctrine, state law, and human rights. In Islamic legal tradition, lineage is established only through a valid marriage (nikah sahih), with children born outside marriage attributed solely to the mother in order to preserve the sanctity of marriage and the clarity of descent. By contrast, Indonesia’s legal framework experienced a significant transformation following Constitutional Court Decision No. 46/PUU-VIII/2010, which amended the Civil Code and the 1974 Marriage Law. The ruling allows children born outside marriage to establish a civil relationship with their biological father if paternity is proven through scientific evidence or acknowledgment. This judicial interpretation diverges sharply from the Compilation of Islamic Law (KHI), which continues to uphold classical fiqh principles. Employing a doctrinal and comparative legal methodology, this study analyzes primary sources including the Qur’an, Hadith, classical fiqh, the Indonesian Constitution, statutory law, the KHI, and the Constitutional Court’s ruling alongside relevant secondary literature. The findings reveal a persistent tension between Islamic law, which confines legitimate paternity to marital bonds, and Indonesia’s evolving legal orientation toward the protection of children’s rights and identity. This duality generates legal uncertainty and underscores the need for harmonization between religious and state frameworks. The paper concludes that a more integrative legal approach is required—one that reconciles Islamic principles with the universal imperative to safeguard every child’s rights and welfare, regardless of birth circumstances.